Pemaafan (Forgiveness) dan Resiliensi (Recilience) pada Pelajar yang mengalami Social Media Fatigue dimasa Pandemi Covid-19 - Hafnidar, H; Junita, Nursan; Zahara, Cut Ita (Journal of Psychological Perspective, 2021)
During the Covid-19 pandemic, communication technology increasingly controls all aspects of human life, in order to achieve success in studying, resilience is essential for Indonesian students. This study aims to empirically test the relationship between forgiveness and resilience in students who experience social media fatigue measured by the Social Media Fatigue Scale that the author created himself based on Bright (2015) concept. A total of 279 Indonesian students spread across several cities in Sumatra and Java, Indonesia, were respondents to the study. Data collection using Forgiveness Scale (4 items, a= 0.829) and Resilience Scale (7 items, a= 0.899), which researchers created based on forgiveness theory which developed by Enright (2001) and McCullough, et al (1998) and resilience theory which developed by Reivich and Shatte (2002). The results of a simple regression test showed a significant positive relationship between forgiveness and resilience (R= .781; p less than 0.001; F=18.03) where the effective contribution of forgiveness to resilience is 33.9%. The implications of the results of the study will be discussed.  Abstrak: Masa pandemic Covid-19 teknologi komunikasi semakin mengontrol segala aspek kehidupan manusia, untuk mencapai keberhasilan dalam belajar, resiliensi sangat diperlukan pelajar Indonesia. Penelitian ini bertujuan untuk menguji secara empirik hubungan antara pemaafan dengan resiliensi pada pelajar yang mengalami social media fatigue berdasarkan Skala Social Media Fatigue yang penulis buat sendiri dari konsep Bright (2015). Sebanyak 279 orang pelajar Indonesia yang tersebar di beberapa kota di Pulau Sumatera dan Jawa, Indonesia, menjadi responden penelitian. Pengumpulan data menggunakan Skala Pemaafan (Forgiveness Scale, 14 aitem, a= 0.829) dan Skala Resiliensi (Recilience Scale, 7 aitem, a= 0.899), yang peneliti buat sendiri berdasarkan Teori Forgiveness yang dikembangkan oleh Enright (2001) dan McCullough, dkk (1998) dan Teori recilience dari Reivich dan Shatte (2002). Hasil uji regresi sederhana menunjukkan adanya hubungan positif yang signifikan antara pemaafan dengan resiliensi (R= .781; p kurang dari 0.001; F=18.03) dimana sumbangan efektif pemaafan terhadap resiliensi sebesar 33.9%. Implikasi hasil penelitian akan didiskusikan.